Analisis Strategi Modern dalam Manajemen Promosi Ritel Alfamart - Gede Okta Wardana; Reza Aryantov; Adhi Satya Nugraha; Indra Kurniawan; Ilham Fahrezi; Nuris Sanida; Iskandar Ali Alam; Defrizal Defrizal (Jurnal Pengabdian Masyarakat, 2026)
Alfamart, one of the largest retail chains in Indonesia, continuously strives to optimize its promotional management strategy to enhance its competitiveness in an increasingly dynamic and competitive retail market. The rapid development of modern retail and shifting consumer behavior require companies such as Alfamart to continuously innovate in designing effective promotional strategies that are not only attractive but also capable of influencing purchasing decisions and strengthening long-term customer relationships. This article discusses innovation and the implementation of modern promotional management strategies applied by Alfamart, as well as their impact on sales performance and customer loyalty. The discussion focuses on how promotional programs are designed, implemented across retail outlets, and how these strategies contribute to improving consumer engagement, increasing sales volume, and strengthening brand positioning in the retail industry. Using a literature review approach, this article analyzes various relevant academic sources, industry reports, and previous studies to provide an in-depth understanding of Alfamart’s promotional strategies. The findings indicate that integrated and well-structured promotional management plays a significant role in increasing sales, improving customer satisfaction, and strengthening customer loyalty, while promotional innovation is a key factor in maintaining Alfamart’s competitiveness in the evolving retail landscape.